The Influence of Organizational Commitment, Intrinsic Motivation, and Extrinsic Motivation on Job Satisfaction Among Employees of PT Surganya Motor Indonesia - Hartatok, Dedi; Kurniawan, Ignatius Soni; Septyarini, Epsilandri (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
The phenomenon of low employee job satisfaction remains a common issue faced by many companies, including those in the automotive retail industry such as PT Surganya Motor Indonesia. This study aims to examine the influence of organizational commitment, intrinsic motivation, and extrinsic motivation on employee job satisfaction. A quantitative approach was employed using a survey method, with a sample of 112 employees working at outlets along the Ringroad in Yogyakarta. The sampling technique used was a census method, involving all employees who met the research criteria without applying any selection or sampling. The research instrument was a questionnaire using a Likert scale, and the data were analyzed using multiple linear regression. The results show that organizational commitment, intrinsic motivation, and extrinsic motivation have a positive and significant effect on job satisfaction, both simultaneously and partially, with extrinsic motivation being the most dominant factor. These findings may provide valuable input for similar companies in improving employee job satisfaction through the strengthening of commitment and motivation.